2019
DOI: 10.1109/jpets.2019.2935703
|View full text |Cite
|
Sign up to set email alerts
|

Sampling-Based Model Predictive Control of PV-Integrated Energy Storage System Considering Power Generation Forecast and Real-Time Price

Abstract: This paper proposes a novel control solution designed to solve the local and grid-connected distributed energy resources (DERs) management problem by developing a generalizable framework capable of controlling DERs based on forecasted values and real-time energy prices. The proposed model uses sampling-based model predictive control (SBMPC), together with the real-time price of energy and forecasts of PV and load power, to allocate the dispatch of the available distributed energy resources (DERs) while minimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…On the technical side, RTC for batteries has been implemented through Model Predictive Control (MPC) [23], [24], or through heuristic rules [17], [25], and can consider battery degradation [24], [26] or not. Although it is relevant to study batteries degradation depending on the use of the battery [4], it was shown that for grid applications with currently commercialised residential batteries, it is usually not more financially profitable to consider battery degradation in the battery control algorithm [5], [8], [27].…”
Section: Nomenclaturementioning
confidence: 99%
See 1 more Smart Citation
“…On the technical side, RTC for batteries has been implemented through Model Predictive Control (MPC) [23], [24], or through heuristic rules [17], [25], and can consider battery degradation [24], [26] or not. Although it is relevant to study batteries degradation depending on the use of the battery [4], it was shown that for grid applications with currently commercialised residential batteries, it is usually not more financially profitable to consider battery degradation in the battery control algorithm [5], [8], [27].…”
Section: Nomenclaturementioning
confidence: 99%
“…, that will be sent as a setpoint to the Battery Power Management System (PMS) of the household's battery. Unlike previous implementations of MPC for battery control that consider either a single objective of bill reduction or self-consumption [23], [24], or that aim to regulate the grid through balancing frequency or voltage [32], [33], the proposed algorithm includes two objectives, i.e. the maximisation of self-consumption at the household level, but also the integration of the market commitments, which can imply the need for charging or to empty the battery at a given time.…”
Section: A Model-predictive Control Algorithmmentioning
confidence: 99%
“…Both subsystems have support for multiple industrial protocols utilized for the communications between the physical or simulated EPS assets. Advanced control schemes and experimentation with communication network components are also supported via HIL simulations [31], [73]. Additionally, the impact of unexpected failures or cyber-attacks targeted at these components can be examined in a controlled environment where minimum risk exists [32].…”
Section: A Cpes Testbedsmentioning
confidence: 99%
“…Authors [9] have thoroughly investigated the effective way of energy production, capital and investment costs, efficiency, discount rate, and LCOE of solar, wind, and hydrogen fuel cell-based hybrid microgrid systems where different energy generation scenarios are investigated for maximum RE utilization [10]. An innovative approach to energy management was developed by the Authors [11,12] to calculate the optimal use of PV/ wind/biomass and energy storage among other distributed energy resources (DERs) and to develop a control scheme that utilizes Sampling-Based Model Predictive Control and recasts the problem as a graph search where real-time data from Florida state was used. Researchers [13] present economic dispatch and power management solutions using Model Predictive Control models for solving a mixed-integer nonlinear programming problem for stand-alone microgrids with a diesel generator, PV, wind, and energy storage systems to calculate operational and maintenance costs (O&M), cost of energy, and net present cost.…”
Section: Introductionmentioning
confidence: 99%